Utilization of agro-industrial residues for improved lipase production by a halo-thermotolerant bacillus amyloliquefaciens - Kelly, Lai Jie Jing (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Lipase is the main biocatalyst within the various industrial enzymes with proven industrial applications. The aim of this work was to produce halo-thermotolerant lipases by solid-state fermentation (SSF) using agro-industrial residues by Bacillus amyloliquefaciens. Seven agro-industrial residues substrates (coconut oil cake, coconut fibre, banana peels, oil palm empty fruit bunch, palm kernel cake, rice husk and sugarcane bagasse) were selected for solid state production of lipase at 37C and 150 rpm. Among the tested supporting matrixes, coconut fibre with agitation SSF was found to be yielded maximum lipase and hence it was selected for further study. The effect of carbon source concentration, incubation temperature, agitation speed, sodium chloride (NaCl) concentration and carbon source concentration were evaluated using one-factor-at-a-time technique. The maximum amount of lipase production was 0.1553 U/ml when glucose as carbon source, incubation temperature of 40C, agitation speed of 200 rpm, 9% (w/v) NaCl concentration and 6% (w/v) glucose concentration were utilized. The thermostability of lipase from B. amyloliquefaciens showed active and stable in the temperature range from 30 to 60C and its maximum lipolytic activity was at 60C. Thus, it was observed that lipase from B. amyloliquefaciens was influenced by different cultural and process parameters. This study proposed the enzyme to be thermostable lipase.